Effect of rpoS Mutation on the Stress Response and Expression of Virulence Factors in Pseudomonas aeruginosa - Suh, Sang-Jin (American Society for Microbiology, 1999)
The sigma factor RpoS (ς(S)) has been described as a general stress response regulator that controls the expression of genes which confer increased resistance to various stresses in some gram-negative bacteria. To elucidate the role of RpoS in Pseudomonas aeruginosa physiology and pathogenesis, we constructed rpoS mutants in several strains of P. aeruginosa, including PAO1. The PAO1 rpoS mutant was subjected to various environmental stresses, and we compared the resistance phenotype of the mutant to that of the parent. The PAO1 rpoS mutant was slightly more sensitive to carbon starvation than the wild-type strain, but this phenotype was obvious only when the cells were grown in a medium supplemented with glucose as the sole carbon source. In addition, the PAO1 rpoS mutant was hypersensitive to heat shock at 50°C, increased osmolarity, and prolonged exposure to high concentrations of H(2)O(2). In accordance with the hypersensitivity to H(2)O(2), catalase production was 60% lower in the rpoS mutant than in the parent strain. We also assessed the role of RpoS in the production of several exoproducts known to be important for virulence of P. aeruginosa. The rpoS mutant produced 50% less exotoxin A, but it produced only slightly smaller amounts of elastase and LasA protease than the parent strain. The levels of phospholipase C and casein-degrading proteases were unaffected by a mutation in rpoS in PAO1. The rpoS mutation resulted in the increased production of the phenazine antibiotic pyocyanin and the siderophore pyoverdine. This increased pyocyanin production may be responsible for the enhanced virulence of the PAO1 rpoS mutant that was observed in a rat chronic-lung-infection model. In addition, the rpoS mutant displayed an altered twitching-motility phenotype, suggesting that the colonization factors, type IV fimbriae, were affected. Finally, in an alginate-overproducing cystic fibrosis (CF) isolate, FRD1, the rpoS101::aacCI mutation almost completely abolished the production of alginate when the bacterium was grown in a liquid medium. On a solid medium, the FRD1 rpoS mutant produced approximately 70% less alginate than did the wild-type strain. Thus, our data indicate that although some of the functions of RpoS in P. aeruginosa physiology are similar to RpoS functions in other gram-negative bacteria, it also has some functions unique to this bacterium.